Literasi Keuangan pada Generasi Milenial - Ningtyas, Mega Noerman (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2019)
Low financial literacy will have an impact on making decisions in daily life. Making wrong decisions will end in poor and ineffective economic management that can lead to financial vulnerable behavior and crises and potentially suffer losses due to financial sector crime. The level of financial literacy will vary according to the demographics. Women, minorities and low income tend to have low levels of financial literacy. Likewise with age, age determines the point of view of people towards something. Generation Y is the generation born in the years 1980-1994 where this generation is very closely related to technology and has different habits with other generations. The purpose of this study is to measure the financial literacy index in the millennial generation. This study uses a type of descriptive research so that researchers describe the index that has been calculated previously. Then it tested for its effect on financial behavior. The test results show basic and sharia financial literacy has a significant positive effect on financial behavior. It show by thet value of both variables are greater than t table (3.147> 1.97; 2.512> 1.97). The more someone understands the financial concept, the more he is able to manage his finances well.